Entrepreneurial Team: How Human and Social Capital Influence Entrepreneurial Opportunity Identification and Mobilization of External Resources - Ahlem Omri; Younes Boujelbene (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Entrepreneurial teams play an extremely important role in the development of any country, especially in developing countries. To understand entrepreneurial teams that operate in a low-technology industry, we rely on the network and human perspective on entrepreneurship. In this paper, we investigate how the social and human capital of entrepreneurial team members influences their ability to identify entrepreneurial opportunities and mobilize external resources. We extend prior research in two ways. First, by using the ordered probit method to measure the identified entrepreneurial opportunities number at the level of entrepreneurial teams. Second, to our knowledge, there is a very small number of studies that have theoretically and empirically investigated the mobilization of external resources, especially at the level of entrepreneurial teams.